Effects of electromagnetic field (EMF) on histological changes and norepinephrine levels in the brains of adult male rats - Yanti Rosli; Hui, Chin Yap; Asmah Hamid; Farah Wahida Ibrahim; Nor Fadilah Rajab (Penerbit UKM, 2016)
The emergence of research about the biological effects of electromagnetic field (EMF) have growing concern among researchers. The aim of this study was to investigate the effects on the brain of rats periodically exposed to 0.1 mT EMF. Total 24 adult male Sprague Dawley rats were subdivided randomly to 4 groups: 2 control groups (C1 6 hours: 6 h/ day for 5 days; C2 20 hours: 20 h/day for 5 days) and 2 treatment groups which exposed to 0.1 mT EMF (T1 6 hours: 6 h/day for 5 days; T2 20 hours: 20 h/day for 5 days). A significant decrease in the pyramidal cell number was higher as the exposure duration to EMF was extended (T1, p<0.05; T2, p<0.001). The total numbers of pyramidal cells for T1 was 15.18 % lower than of the total found in C1; and in concurring to the pattern, the number of pyramidal cells in T2 was 33.54 % lower than the total in C2. Similarly, there was a significant decrease of the Purkinje cell number as the duration exposure to EMF, extended (T1, p<0.05; T2, p<0.001). The total numbers of Purkinje cells for T1 was 11.20 % lower than C1, in T2 was 16.19 % lower than in C2. There were significant differences between the thickness of granular layer and molecular layer in the control groups and treatment groups. We also report a significant difference in the levels of norepinephrine in T2, 10.71 % higher than C2. Cumulatively, these results suggested that exposure to EMF can exert negative effect on rats brains.